2018
DOI: 10.1186/s13054-018-2278-4
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline in critically ill patients on continuous renal replacement therapy: a population pharmacokinetic study

Abstract: BackgroundTigecycline is a vital antibiotic treatment option for infections caused by multiresistant bacteria in the intensive care unit (ICU). Acute kidney injury (AKI) is a common complication in the ICU requiring continuous renal replacement therapy (CRRT), but pharmacokinetic data for tigecycline in patients receiving CRRT are lacking.MethodsEleven patients mainly with intra-abdominal infections receiving either continuous veno-venous hemodialysis (CVVHD, n = 8) or hemodiafiltration (CVVHDF, n = 3) were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 19 publications
(26 reference statements)
1
67
0
Order By: Relevance
“…To date there have been no studies on the adsorption of tigecycline on the filter membranes used for CRRT. Broeker et al [27] report that during the pharmacokinetic assessment of tigecycline during CRRT using PS filters in a group of 11 patients, one of the patients experienced a time delay in the effluent concentrations of tigecycline, which may have been caused by adsorption losses. In our study, a statistically significant, substantial adsorption was observed (more than 95%) for the AN69ST membrane.…”
Section: Discussionmentioning
confidence: 99%
“…To date there have been no studies on the adsorption of tigecycline on the filter membranes used for CRRT. Broeker et al [27] report that during the pharmacokinetic assessment of tigecycline during CRRT using PS filters in a group of 11 patients, one of the patients experienced a time delay in the effluent concentrations of tigecycline, which may have been caused by adsorption losses. In our study, a statistically significant, substantial adsorption was observed (more than 95%) for the AN69ST membrane.…”
Section: Discussionmentioning
confidence: 99%
“…All methods, SE, BS, LLP, BAY, SE-SIR, BS-SIR and LLP-SIR, were also applied to a clinical dataset example [5] and the 95% CI by the different methods were compared. The dataset originating from a hemodialysis study with 11 patients contained 180 blood and 109 dialysate samples thereby represented a typical example for a small-n study.…”
Section: Clinical Dataset Examplementioning
confidence: 99%
“…Nonlinear mixed-effects modelling has gained an important role in quantitative clinical pharmacology, drug development and therapeutic drug use [1,2]. In many applications when non-linear mixed effects modelling is employed, small datasets containing ten or even fewer subjects appear regularly [3][4][5], for example due to ethical concerns, high risks, high costs, low availability of patient (sub)groups of interest to the study or multiple factors. Conclusions drawn from such 'small-n' studies depend on the estimated parameters as well as parameter uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Broeker et al conclude that tigecycline (TGC) losses during continuous renal replacement therapy (CRRT) are comparable to those of patients with normal renal function, indicating that no dose adjustment of TGC is necessary during CRRT [1]. We would like to make some comments.…”
mentioning
confidence: 96%